2015
DOI: 10.1002/etc.3147
|View full text |Cite
|
Sign up to set email alerts
|

Complex mixtures, complex responses: Assessing pharmaceutical mixtures using field and laboratory approaches

Abstract: Pharmaceuticals are present in low concentrations (<100 ng/L) in most municipal wastewater effluents but may be elevated locally because of factors such as input from pharmaceutical formulation facilities. Using existing concentration data, the authors assessed pharmaceuticals in laboratory exposures of fathead minnows (Pimephales promelas) and added environmental complexity through effluent exposures. In the laboratory, larval and mature minnows were exposed to a simple opioid mixture (hydrocodone, methadone,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 75 publications
(189 reference statements)
1
31
0
Order By: Relevance
“…Interestingly, the presence and total concentrations of CECs (Figure ; Fairbairn et al ) appeared to have little impact on the observed patterns of biological responses in fathead minnow bioassays. Even though prior studies (Painter et al ; Schoenfuss et al ) found reduced predator escape performance in the presence of elevated pharmaceutical and estrogenic contamination, fathead minnow feeding, growth, and escape performance were among the highest responses in early summer samples despite the relatively enhanced presence of pharmaceuticals and pesticides, many of which are known estrogens (Figure C and Table ; Fairbairn et al ). Even mean total CEC concentration, which was second highest in the early summer samples, did not appear to affect the fathead minnow bioassays.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Interestingly, the presence and total concentrations of CECs (Figure ; Fairbairn et al ) appeared to have little impact on the observed patterns of biological responses in fathead minnow bioassays. Even though prior studies (Painter et al ; Schoenfuss et al ) found reduced predator escape performance in the presence of elevated pharmaceutical and estrogenic contamination, fathead minnow feeding, growth, and escape performance were among the highest responses in early summer samples despite the relatively enhanced presence of pharmaceuticals and pesticides, many of which are known estrogens (Figure C and Table ; Fairbairn et al ). Even mean total CEC concentration, which was second highest in the early summer samples, did not appear to affect the fathead minnow bioassays.…”
Section: Discussionmentioning
confidence: 82%
“…Fathead minnow were obtained from Environmental Testing and Consulting. All exposures began with larvae <24 h post hatch and lasted 21 d following established protocols (Painter et al ; Schoenfuss et al ). Larval fish were randomly distributed to 1‐L treatment jars (3 jars/treatment, 20 larvae/jar) each containing 0.6 L stormwater.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wastewater effluents and other pollutant sources are often composed of highly complex mixtures, and interactions between EDCs and of EDCs with other chemicals could alter their biological effects (Keiter et al, 2012;Schoenfuss et al, 2015). The potential for additive effects of EDCs and other chemicals is significant.…”
Section: (4) Interactive Mixtures Of Edcsmentioning
confidence: 99%
“…Over the past decade published work on EDCs has provided a strong mechanistic understanding of exposure effects (Colborn, vom Saal & Soto, 1993;Tyler, Jobling & Sumpter, 1998;Kloas et al, 2009;Orton & Tyler, 2012;Tijani, Fatoba & Petrik, 2013). Far less consideration, however, has been given to processes and interactions controlling the effects of EDCs at broader ecological scales, including inter-and intra-specific interactions within populations and food webs (Segner, 2011;Brodin et al, 2014;Schoenfuss et al, 2015). Understanding the effects of EDCs on processes operating at these broader scales is essential, but also challenging, because their effects can be pervasive and they are generally sub-lethal in nature.…”
Section: Introductionmentioning
confidence: 99%